Răspunsuri

Cel mai inteligent răspuns!
2014-06-10T17:12:20+03:00
X/3*(x+1)=4
x(x+1)=3*4
x(x+1)=12
x^2+x-12=0
delta=b patrat-4ac
delta=1-4*1*(-12)
delta=1+48
delta=49

x1=-b- radical din delta/2a
x1=-1-7/2
x1=-8/2
x1=-4

x2=-b+ radical din celta/2a
x2=-1+7/2
x2=6/2
x2=3
===========================
5 supra x+2 din 3x+2 este 10
5(3x+2)/x+2=10
15x+10=10(x+2)
15x+10=10x+20
15x-10x=20-10
5x=10
x=10:5
x=2
=====================================
x+1 supra x +2 din 2x+4 este 12
(2x+4)(x+1)/x+2 = 12
2(x+2)(x+1)/x+2=12    x+2 se simplifica
2(x+1)=12
2x+2=12
2x=12-2
2x=10
x=10:2
x=5

2 5 2